Method for preparing autoclaved aerated concrete from unburned coal gangue

The oxidation treatment of coal gangue by chemical decarbonization modification activator solves the problems of high carbon content and low volcanic ash activity in autoclaved aerated concrete, and achieves efficient resource utilization and environmental protection improvement, solving the problem of Environmental pollution and energy waste in industrial production.

CN119118553AActive Publication Date: 2024-12-13BEIJING DUCHENG TECHNOLOGY DEVELOPMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410645836.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2024-12-13
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

In the prior art, the utilization of coal gangue in the field of autoclaved aerated concrete has problems such as high carbon content, low volcanic ash activity, and environmental pollution and energy waste caused by combustion treatment, making it difficult to achieve industrial production.

Method used

Use chemical decarbonization modified activators, such as nitrates, peroxides or permanganate, to oxidize coal gangue, reduce carbon content and stimulate mineral activity, form microporous structures, and increase the strength of autoclaved aerated concrete and hydration reaction effect.

Benefits of technology

It improves the tolerance and utilization rate of coal gangue in autoclaved aerated concrete, achieves a high proportion of resource utilization, reduces environmental pollution and energy consumption, and improves the physical performance and environmental protection of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118553A_ABST
    Figure CN119118553A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of decarbonization modification activation treatment of unburned coal gangue and preparation of autoclaved aerated concrete. The unburned coal gangue decarburization modifier is any one of nitrate, potassium permanganate, H2O2 and the like. The invention relates to an unburned coal gangue decarburization modification activation method, which comprises composite decarburization modification activation such as physical decarburization, mechanical activation, chemical decarburization modification activation and the like. The autoclaved aerated concrete prepared from the unburned coal gangue comprises more than 50% of the decarburized modified activated gangue material. According to the invention, the tolerance of the product to the carbon content of the coal gangue is improved, the activity of the coal gangue raw material is excited, the hydrothermal reaction is promoted to be fully carried out, and a multi-mineral gelling substance composed of several kinds of hydrated calcium silicate and other hydrated minerals can be generated, so that a more compact microcrystalline structure is obtained; and the formation of a micropore structure in a pore wall is facilitated, so that the product has good physical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a technology for chemically decarbonizing, modifying and activating coal gangue, and a technology for preparing autoclaved aerated concrete by using the decarbonized modified coal gangue. Background Art

[0002] Since the beginning of the new century, many hardworking and intelligent people have adopted new technologies and even introduced foreign production technologies and equipment to produce batches of new energy-saving building materials based on the benefits of waste utilization and environmental protection, or policies such as energy conservation, emission reduction and improvement of building functions. For example: hollow bricks, sand-lime bricks, (waste blended) concrete bricks, lightweight concrete blocks, aerated concrete blocks, lightweight composite insulation blocks, composite panels, EPS insulation boards, phenolic boards, XPS extruded boards, polyurethane boards, foamed cement, rock wool boards, foam glass and other new building materials in full bloom.

[0003] It is undeniable that many new building materials have made important contributions to the comprehensive utilization of waste, energy conservation and emission reduction, and even the development of modern building technology. However, some materials have disadvantages such as high water absorption, flammability, aging, peeling, and high thermal conductivity, which have caused significant losses to the national economy and people's lives and property, and have become a criticism of new energy-saving materials.

[0004] According to statistics, the total building area in my country has reached more than 60 billion square meters, and is growing at a rate of about 2 billion square meters per year. Building energy consumption accounts for 27.5% of the total social terminal energy consumption, not including the energy consumption in the production of building materials and construction. Therefore, building energy conservation is an important measure for the country and an important national policy.

[0005] Building energy conservation refers to reducing energy consumption as much as possible while meeting the same needs or achieving the same purpose during the production of building materials, construction of houses and structures, and use. It is usually achieved by improving the thermal insulation and sealing of building walls, doors, windows, roofs and other enclosures, and reducing the energy consumption of heating, air conditioning and other facilities to improve the living environment and save energy.

[0006] However, the short-term energy-saving goal has been achieved, and the comprehensive evaluation of the energy-saving effect of the entire life cycle of the building must not be ignored, and the overall goal of "health, comfort, beauty, durability, safety, economy, and environmental protection" cannot be biased. Therefore, the ideal new energy-saving and environmentally friendly ecological building materials should have comprehensive functions such as light weight and high strength, fireproof and non-combustible, waterproof and breathable, heat insulation, sound insulation and sound absorption, weather resistance and durability, economy and environmental protection.

[0007] Obviously, autoclaved aerated concrete ecological building materials are the most excellent new ecological materials with this comprehensive feature.

[0008] Autoclaved aerated concrete is a recognized green ecological wall material with the advantages of light weight, heat insulation, thermal insulation, sound insulation, fire resistance, impermeability, earthquake resistance, environmental protection, durability, economy, and convenient construction. It plays an irreplaceable role in the field of wall innovation and energy-saving construction.

[0009] Steam-pressurized concrete is a porous silicate product made of siliceous and calcareous materials as the main raw materials, mixed with gas-generating agents, and manufactured through processes such as raw material preparation, batching and pouring, gas generation and quiescence, cutting and forming, autoclaving and curing, sorting and packaging. Its typical feature is that the pores in the product are formed by chemical reactions.

[0010] We divide the raw materials used in the production of autoclaved aerated concrete into four categories: basic materials, gas-generating materials, regulating materials and structural materials. Basic materials are the main materials that form autoclaved aerated concrete, accounting for more than 95% of the total weight of the product, including siliceous materials (the main component is SiO 2 ) and calcareous materials (mainly CaO). The source of siliceous materials is generally quartz sand, accounting for 55-65% of the product weight. The source of calcareous materials is mainly cement and lime, accounting for more than 30% of the product weight.

[0011] Since sand is a non-renewable mineral resource, not only is its cost high, but it is also strictly controlled by the state. 2 and Al 2 O 3 The total content is above 70%, and some exceed 90%. 2 The content is generally above 50%, and some even reach 80%. It can be seen that the use of coal gangue as a siliceous material for the production of autoclaved aerated concrete is innately qualified. Therefore, the development of coal gangue to replace siliceous materials not only finds an effective way to save energy, save soil, recycle waste, and protect the environment, but also finds a sustainable development path for autoclaved aerated concrete production enterprises to reduce costs and improve benefits.

[0012] However, compared with other minerals with volcanic ash activity (including fly ash from power plants), the minerals that make up coal gangue are often better crystallized, the chemical molecules are arranged in a more orderly and dense manner, and their chemical structure is relatively stable. Therefore, the volcanic ash activity of the original coal gangue is very low. At the same time, since coal gangue generally contains combustible carbon, it creates certain obstacles for the direct use of coal gangue. The carbon content of Class I and Class II coal gangue is ≤6% (the lower calorific value is below 420kcal); while the carbon content of Class III coal gangue is 6% to 20%, which is between Class II and Class IV coal gangue; the carbon content of Class IV coal gangue is ≥20%, and the calorific value is higher (lower calorific value ≥1400kcal / kg).

[0013] Because of the above reasons, the current use and research of coal gangue in the field of autoclaved aerated concrete generally uses coal gangue after spontaneous combustion, or uses combustion method to pre-treat the coal gangue.

[0014] After the gangue is spontaneously combusted, the problem of its carbon content has been basically solved, and the activation problem of raw materials has also been improved to a certain extent. According to data, 237 gangue mines in my country have experienced spontaneous combustion, and there are still 134 gangue mountains that have spontaneous combustion to varying degrees. However, the spontaneous combustion of gangue not only wastes precious coal resources, but also emits carbon dioxide, sulfur dioxide, nitrogen oxides and smoke during the combustion process, which seriously pollutes the atmospheric environment and endangers the health of people in the mining area. At the same time, spontaneous combustion of gangue is highly regional, specific and incomplete. Therefore, some researchers took the preparation of spontaneous combustion gangue autoclave aeration as one of the specific objects and conducted the following research.

[0015] After the gangue is burned, on the one hand, the influence of carbon on product quality is eliminated, and on the other hand, minerals such as calcite and illite can be decomposed, which increases the volcanic ash activity of the gangue. This can kill two birds with one stone and solve the problems of carbon content and raw material activity in the comprehensive utilization of gangue. However, the process of thermal activation not only consumes a high amount of energy, but also causes secondary waste of energy if the heat generated by combustion cannot be effectively utilized. Moreover, during the high-temperature calcination process, chemical substances that are harmful to the human body and pollute the environment will be released. The application process is cumbersome and uneconomical, which increases the pressure of carbon emissions and does not conform to the current development trend of my country. Therefore, the research on the preparation of autoclaved aerated concrete using thermally activated gangue technology can only remain in the laboratory. It is not only not environmentally friendly and uneconomical for large-scale industrial production, but also has certain technical risks.

[0016] Professor Wang Changlong and Qiao Chunyu of Beijing University of Science and Technology and Hebei University of Engineering conducted experimental research on the preparation of autoclaved aerated concrete using coal gangue and iron tailings. The optimized scheme used 20% coal gangue (40% iron tailings). The method is as follows: (1) Pretreatment of raw materials: crush the coal gangue to less than 2 mm and then dry it to a moisture content of less than 1%. Then use a SMS 500mm×500mm laboratory ball mill with a charge of 5kg. The fineness of the coal gangue after grinding is less than 8% of the residue on a 0.08mm square hole sieve. Use a CD-1400X muffle furnace for calcination and activation. The calcination temperature is 600℃ and the temperature is kept for 4h. The calcined coal gangue is water quenched and cooled to room temperature. After drying the iron tailings, use a SMS 500mm×500mm laboratory ball mill to grind the coal gangue to a fineness of less than 7.5% on a 0.08mm square hole sieve. (2) Preparation of ingredients: The calcined coal gangue and finely ground iron tailings are used as the main siliceous raw materials for batching. The final optimized batching scheme is (mass fraction): coal gangue / iron tailings / lime / gypsum = 20 / 40 / 25 / 10 / 5, the amount of aluminum powder paste is 0.06% of the total weight of the blank, the amount of water added is 0.60 of the total amount of dry material, the pouring temperature is 55°C, and the static curing temperature is 55°C. The autoclave curing conditions are: heating for 2h, constant temperature and pressure for 8h (temperature 185°C, maximum pressure 1.25Mpa), and cooling for 2h. The products meet the requirements of A3.5 and B06 grade qualified products in "Autoclaved Aerated Concrete Blocks" (GB 11968-2006).

[0017] Cong Xinyu and others from Harbin Institute of Technology used self-igniting coal gangue from a coal mine in Dalianhe Town, Heilongjiang Province to conduct experiments on autoclaved aerated concrete. They found that under the condition of taking both compressive strength and dry density into consideration, the optimal mix ratio of coal gangue / quicklime / cement / gypsum is 54 / 23 / 20 / 3, and the aluminum powder content is 1.3‰ of the total amount of matrix material. At this time, the calcium-silicon ratio of the matrix material is 0.82.

[0018] In the above-mentioned related technologies, the amount of coal gangue treated by combustion method is only 20%; although the amount of spontaneous combustion coal gangue reaches 54%, it cannot be adapted to industrial production due to the insufficiency and unevenness of spontaneous combustion coal gangue. Therefore, the amount of mixing is relatively low in resource utilization and cannot be applied on a large scale. At the same time, the use of combustion method to treat coal gangue not only wastes precious coal resources, but also emits carbon dioxide, sulfur dioxide, nitrogen oxides and smoke during the combustion process, seriously polluting the atmospheric environment. Summary of the invention

[0019] After long-term research, the inventors of the present invention found that under the action of an oxidant, coal in coal gangue will be oxidized. Its oxidation process is from surface oxidation to mild oxidation, moderate oxidation, deep oxidation and finally complete oxidation. Its molecular structure changes from complex to simple. The higher the oxidation temperature, the stronger the oxidant, and the longer the oxidation time, the simpler the molecular structure of the oxidation product. From complex humic acid to simple low molecular weight acid, until it is finally completely oxidized into carbon dioxide and water.

[0020] It was further found that the oxidation conditions of coal in coal gangue are:

[0021] It can be oxidized in strong oxidant (such as nitric acid) solution at 60-100℃;

[0022] 100-200℃ can be oxidized by air and oxygen in alkaline solution;

[0023] 100-300℃ can be oxidized by direct air and oxygen;

[0024] It can be oxidized by air oxygen in pressurized alkaline solution at 200-300℃.

[0025] At all stages, increasing the oxidant strength, increasing the amount of oxidant, extending the reaction time, increasing the oxidation temperature, adding stirring measures, and increasing the reaction pressure can promote the speed and efficiency of oxidation.

[0026] The inventors found through experimental research that using 7% H 2 O 2 The gangue is oxidized at 60℃~80℃ for 12h, and the coal carbon structure in the gangue is destroyed as a whole. More than 90% of the coal carbon in the original gangue is moderately to deeply oxidized, and the macromolecules are converted into small molecules. With the addition of cement and lime alkaline materials, and even after the gangue autoclaved aerated concrete body enters the autoclave for further pressurization and temperature increase, the residual coal carbon and its oxidation products (small molecular acids, etc.) in the body are further oxidized and decomposed until they are completely oxidized to CO 2 and H 2 O.CO 2 and H 2 After O volatilizes, part of the space occupied by these products may become micropores in the pore wall of coal gangue autoclaved aerated concrete.

[0027] The study also found that as the coal in the gangue is continuously oxidized, the mineral structure of the gangue, such as calcite and illite, disintegrates and decomposes as the gangue is stripped, thereby promoting the SiO 2, CaO and other elements. According to the pore wall structure theory of autoclaved aerated concrete, we know that if the porosity is kept unchanged, the pore content is reduced, and the capillary pores and micropores are increased, the strength of autoclaved aerated concrete can be improved. Therefore, the micropores formed by the small molecular products produced after the coal gangue is oxidized by a strong oxidant have become an auxiliary means to reduce the pore size of the coal gangue autoclaved aerated concrete and improve the strength of the coal gangue autoclaved aerated concrete. After the coal gangue is oxidized by a strong oxidant, the minerals that make up the coal gangue disintegrate and decompose, which promotes the SiO 2 We are also happy to see that the depolymerization and activation of elements such as CaO and other elements can improve the hydration reaction effect of gangue autoclaved aerated concrete. Therefore, the strong oxidant introduced in the preparation process of gangue autoclaved aerated concrete not only becomes a decarbonization modifier for gangue, but also becomes a modifier of SiO in gangue. 2 A performance activation stimulant for elements such as Mg and CaO.

[0028] The present invention aims to solve the key problems existing in the process of preparing autoclaved aerated concrete using coal gangue, and provides a method for improving the tolerance of the carbon content of coal gangue in the preparation of autoclaved aerated concrete. It also provides a coal gangue decarbonization, modification and activation treatment technology with an environmentally friendly coal gangue decarbonization treatment method, less coal gangue treatment equipment and high treatment efficiency, and a technology for preparing autoclaved aerated concrete using the above-mentioned coal gangue.

[0029] In view of the above-mentioned limitations, the present invention proposes an unburned coal gangue decarbonization modification activator, a decarbonization modification activation method and an autoclaved aerated concrete prepared therefrom.

[0030] An unburned coal gangue decarbonization modification activator, the unburned coal gangue chemical decarbonization modification activator comprising:

[0031] Group 1: Nitrates;

[0032] and / or, in the second group, peroxides or percarbonates;

[0033] and / or, group III, permanganate;

[0034] The amount of the unburned coal gangue decarbonization modification activator used accounts for 1% to 7% of the total mass of the coal gangue.

[0035] Further: the nitrate includes: at least one of sodium nitrate, calcium nitrate, and calcium ammonium nitrate;

[0036] The percarbonate comprises: at least one of sodium percarbonate and calcium percarbonate;

[0037] The peroxide comprises: H 2 O 2 ;

[0038] The permanganate includes potassium permanganate.

[0039] Further: if the unburned coal gangue decarbonization modification activator is only nitrate, the amount of nitrate used accounts for 1% of the coal gangue

[0040] Total mass, by mass:

[0041] For coal gangue with carbon content of 0% to 5%, use 1% to 3%;

[0042] 2% to 5% of coal gangue with a carbon content of 5% to 10%;

[0043] 3% to 6% of coal gangue with a carbon content of 10% to 15%;

[0044] For coal gangue with a carbon content of 15% to 20%, 4% to 7% is used.

[0045] A method for decarbonizing, modifying and activating unburned coal gangue, the method comprising: chemical decarbonizing, modifying and activating treatment, wherein the chemical decarbonizing, modifying and activating treatment comprises: treating the unburned coal gangue with the unburned coal gangue decarbonizing, modifying and activating agent to obtain decarbonizing, modifying and activating gangue slurry.

[0046] Furthermore: the method also includes: physical decarbonization and / or mechanical activation, and the coal gangue is first treated with physical decarbonization and / or mechanical activation, and then chemical decarbonization modification and activation treatment is performed after the treatment.

[0047] Further: the physical decarbonization is to separate coal and gangue by photoelectric separation, and / or to adopt at least one of screening, wet separation and gravity separation, so that the carbon content of the gangue is the first carbon content;

[0048] The mechanical activation is to hammer the gangue and then further grind it to make the gangue particle size be the first particle size after grinding;

[0049] After the chemical decarbonization, modification and activation treatment, the carbon content of the gangue in the decarbonization, modification and activation gangue slurry obtained is set to the second carbon content.

[0050] Further: the first carbon content is less than 20%; the second carbon content is less than 3%;

[0051] The milling and refining process uses dry milling or wet milling;

[0052] The first particle size is: 180 mesh sieve residue ≤ 15%.

[0053] Furthermore: the chemical decarbonization modification and activation treatment is to add the unburned coal gangue decarbonization modification activator to the unburned coal gangue according to the above-mentioned usage amount, stir it at a temperature of 60°C to 80°C until it is fully reacted, and obtain the decarbonization modification activated gangue slurry with a carbon content of less than 3%, and the decarbonization modification activated gangue slurry contains 30% to 90% silicon oxide, 0.2% to 45% aluminum oxide, and 0.05% to 20% calcium oxide.

[0054] A kind of autoclaved aerated concrete prepared from unburned coal gangue, the ingredients of the autoclaved aerated concrete prepared from unburned coal gangue are:

[0055] Using 50% or more by mass of decarbonized modified activated gangue slurry, wherein the decarbonized modified activated gangue slurry is obtained by the method;

[0056] The calcium / silicon ratio of the ingredients is 0.5-1.0.

[0057] Furthermore: the hydrothermal synthesis product contained in the autoclaved aerated concrete prepared from the unburned coal gangue comprises hydrated mineral crystals, and the hydrated mineral crystals include any combination of CSH(I), tobermorite, aluminum-substituted tobermorite, hydrogarnet, xonotlite, and hydrated calcium sulfoaluminate.

[0058] Furthermore: the autoclaved aerated concrete prepared from the unburned coal gangue forms a heterogeneous solid-liquid-gas multiphase stacking structure with inner core particles of siliceous material as the skeleton, hydrated silicate as the colloid, connected and supported by crystal intergrowths, and including a variety of micropores.

[0059] Compared with the related art, the present invention has the following advantages:

[0060] An unburned coal gangue decarbonization modification activator in one aspect of the present invention, by using the modifier protected by the present application, not only expands the tolerance of the autoclaved aerated concrete manufacturing process to the carbon content of the coal gangue material, but also effectively stimulates and improves the activity of the coal gangue raw material, improves the hydrothermal synthesis reaction effect of the product, generates sufficient hydration products, and can also promote the increase of the micropore content of the pore wall of the autoclaved aerated concrete, thereby facilitating the process control of reducing the large pore content while maintaining the porosity unchanged, so that the product obtains good performance. And the modifier can achieve the effects of decarbonization treatment, activation treatment and micropore manufacturing in one step, so it has great innovative significance. The amount of coal gangue treated with the chemical decarbonization modification agent can reach more than 60%, and the reaction efficiency is high, no additional equipment is required, and the construction investment is reduced. In the preparation of the autoclaved aerated concrete of the present invention, coal gangue is used as the main raw material of siliceous materials, and the content of coal gangue can reach more than 60%. Such a high proportion of resource utilization can greatly solve the problem of coal gangue accumulation. After being treated with the modifier or method of the present invention, the coal gangue raw material for preparing autoclaved aerated concrete can reach more than 60%, which has an unexpected technical effect.

[0061] Another aspect of the present invention is a method for decarbonization, modification and activation of unburned coal gangue and another aspect is an autoclaved aerated concrete prepared from unburned coal gangue. By combining physical decarbonization, mechanical activation, chemical decarbonization, modification and activation and other multi-stage composite decarbonization modification, on the one hand, the utilization rate of coal gangue is improved, and the amount of coal gangue in autoclaved aerated concrete is increased, so that coal gangue can be effectively recycled and the environmental problem of stacking coal gangue is solved. On the other hand, the activity of coal gangue is also improved, so that the physical properties of its autoclaved aerated concrete products are significantly improved. By using the above-mentioned decarbonization modification activator to chemically decarbonize the gangue, not only the tolerance of the autoclaved aerated concrete manufacturing process to the carbon content of the gangue raw material is expanded, and the application of the third type of gangue in autoclaved aerated concrete becomes possible, thereby increasing the processing ratio of the gangue; at the same time, the carbon content of the first and second types of gangue can be further reduced to obtain a higher quality autoclaved aerated concrete product, and the activity of the gangue raw material is effectively stimulated and improved, and the hydrothermal synthesis reaction effect of the product is further improved, and the micropore content of the autoclaved aerated concrete is promoted, thereby improving the physical properties of the autoclaved aerated concrete product. The decarbonization treatment, activation treatment and promotion of micropore content are combined in one step, so it has great innovative significance. The amount of gangue treated by the method of the present invention can reach more than 60%, and the reaction efficiency is high, and no additional equipment is required, which reduces economic investment. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1-1The samples of Experimental Example 1 and Experimental Example 2 were prepared by adding chemical modifiers to 1# coal gangue raw materials. In Experimental Example 2, other modifiers were added to further improve the strength of the product.

[0063] Figure 1-2 The samples of Experimental Example 3 (H3) and Experimental Example 4 (H4) were prepared by adding chemical modifiers to 2# coal gangue raw materials. Among them, Experimental Example 4 (H4) added other modifiers to further improve the strength of the product;

[0064] Figure 1-3 The sample (15-2) of Experimental Example 5 was prepared by adding a chemical modifier to the 3# coal gangue raw material;

[0065] Figure 1-4 The sample of Experiment 6 was prepared by adding other regulators to the raw material of 3# coal gangue on the basis of Experiment 5;

[0066] Figure 2 This is a 40-fold observation photo of 2# coal gangue raw material, in which the black particles are carbon particles;

[0067] Figure 3 The raw material is 3# coal gangue with a carbon content of about 15.4%. After no chemical modification activator is added, after batching, stirring, pouring, stopping, and demoulding, the appearance inspection shows that the sample is unqualified, with poor mechanical strength and uneven bubble distribution. Therefore, no further subsequent processing procedures and inspections are carried out;

[0068] Figure 4 The XRD diffraction pattern of the autoclaved aerated concrete experimental sample prepared from 1# coal gangue in another embodiment of the present invention;

[0069] Figure 5 This is a SEM image of an autoclaved aerated concrete experimental sample prepared with 1# coal gangue according to another embodiment of the present invention. DETAILED DESCRIPTION

[0070] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. However, it should be understood that the description herein is only used to explain the present invention and is not used to limit the scope of the present invention.

[0071] Unless otherwise defined, all technical terms and scientific terms used herein have the same meanings as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The characterization means involved in this article can refer to the relevant descriptions in the prior art and will not be repeated herein.

[0072] In order to further understand the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0073] The inventors of the present invention have found in long-term research that coal gangue is a collection of various sedimentary rocks, and different sedimentary rocks are composed of different diagenetic minerals. Most of the carbon in coal gangue is mixed, interwoven, and wrapped with various minerals such as quartz, alumina, and carbonate in the coal gangue, or mixed in various carbonate mineral phases such as calcite, mica, kaolinite, and illite. Therefore, how to treat coal gangue so that silicon oxide, silicon oxide and other elements in the coal gangue can have higher activity is one of the main research contents of the present invention.

[0074] Example 1

[0075] An unburned coal gangue decarbonization modification activator, the unburned coal gangue decarbonization modification activator comprising:

[0076] Group 1: Nitrates;

[0077] and / or, in the second group, peroxides or percarbonates;

[0078] and / or, group III, permanganate;

[0079] The amount of the unburned coal gangue decarbonization modification activator used accounts for 1% to 7% of the total mass of the coal gangue, by mass, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0080] Further: the nitrate includes: at least one of sodium nitrate, calcium nitrate, and calcium ammonium nitrate;

[0081] The percarbonate comprises: at least one of sodium percarbonate and calcium percarbonate;

[0082] The peroxide comprises: H 2 O 2 ;

[0083] The permanganate includes potassium permanganate.

[0084] Further: If the unburned coal gangue decarbonization modification activator is only nitrate, the amount of nitrate used in the total mass of coal gangue is calculated by mass as follows:

[0085] 1% to 3% of the coal gangue with a carbon content of 0% to 5% is used; for example, it can be 1%, 2%, or 3%. The present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0086] 2% to 5% of the coal gangue with a carbon content of 5% to 10% is used; for example, it can be 2%, 3%, 4%, 5%. The present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0087] 3% to 6% of the coal gangue with a carbon content of 10% to 15% is used; for example, it can be 3%, 4%, 5%, 6%. The present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0088] The coal gangue with a carbon content of 15% to 20% uses 4% to 7%, for example, 4%, 5%, 6%, 7%. The present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0089] Coal is a reducing agent and easily reacts with oxidants. The oxidation of coal not only destroys the structure of coal, but also produces some new substances (including CO 2 , H 2 , O 2 ) and other gases. After research, coal uses H 2 O 2 During oxidation, H 2 O 2 It breaks covalent bonds, such as Ar-OH, Ar-O-Ar and substituted carbon, and then generates -COOH, C-O-C, R-OH. The hydrogen and oxygen absorbed during coal oxidation mainly enter the carbon structure in the form of -OH. First, the weak C-O bond breaks, producing a large number of water-soluble macromolecules and CO 2 , macromolecules gradually decompose into small molecular fatty acids and other substances. Experiments show that under relatively low temperature (100°C), coal can undergo various oxidation reactions with air, oxygen or other strong oxidants. Although the conditions are relatively mild, the structure of coal can be destroyed.

[0090] Coal oxidation is the process of transformation of the molecular structure of coal from complex to simple under the action of oxidants. The higher the oxidation temperature, the stronger the oxidant, and the longer the oxidation time, the simpler the molecular structure of the oxidation product, from complex humic acid to simple benzoic acid, until it is completely oxidized to carbon dioxide and water. 2 O 2 During the 2h oxidation test, 90% of the product was converted into small molecular weight benzoic acid, fatty acid, oxalic acid and other new substances, 17% of the product was soluble in water, and only 10% of the residual coal was left. At this time, the structure of the coal was completely destroyed. 2 In an alkaline environment, especially under autoclave conditions, products such as oxalic acid will continue to undergo oxidation reactions, or generate nano-scale calcium oxalate crystals, or even be completely oxidized to generate carbon dioxide and water.

[0091] According to the above findings, further experiments were conducted. The inventors added appropriate strong oxidants to the gangue to destroy the structure of coal in the gangue. After oxidation, part of the coal generated gas was discharged, thereby reducing the content and impact of coal; and other small molecular substances such as carboxylic acid and oxalic acid generated by oxidation are not only not easy to cause concentrated harm to the products, but even after entering the alkaline environment, with the increase of curing time, curing pressure and temperature, they are completely oxidized to generate carbon dioxide and water. Also, because of this oxidation reaction, the coal is stripped from other mineral bodies, thereby changing the physical and chemical properties of the original minerals (such as illite, mica, coal seam intercalated gangue and other impurity-rich minerals), and it will also depolymerize into highly active components such as silicon oxide, aluminum oxide, and calcium oxide, which is conducive to participating in the hydrothermal synthesis reaction of the product. At the same time, the Al-O and Si-O bonds are broken during the oxidation process, which enhances the volcanic ash activity of the gangue and solves the problem of low volcanic ash activity of the gangue. At the same time, the chemical modification activator does not have other adverse effects on the inorganic mineral raw materials in the gangue.

[0092] Therefore, by adopting the above chemical modifier, not only the tolerance of the carbon content of coal gangue is expanded, and the application of the third type of coal gangue in autoclaved aerated concrete becomes possible, thereby increasing the processing ratio of coal gangue; at the same time, the carbon content of the first and second types of coal gangue can be further reduced, and the amount of coal gangue can reach 50-70% by mass, and the activity of the hydrothermal reaction of the coal gangue raw material is effectively stimulated and increased, and the hydrothermal synthesis reaction effect of the product is further improved, so that it is easy to produce hard tobermorite, aluminum tobermorite, CSH, calcium silicate and hydrated calcium sulfoaluminate and other hydration products together to form a microcrystalline structure formed by multi-minerals and cementitious substances, and it can also promote the formation of the microporous structure of autoclaved aerated concrete, thereby improving the physical properties of concrete products. It has the effects of decarbonization treatment, activation treatment and microporous structure formation in one step, so it has great innovative significance. In the preparation of the autoclaved aerated concrete of the present invention, coal gangue is used as the main raw material of the siliceous material, and the content of coal gangue can reach more than 60%. Such a high proportion of resource utilization can greatly solve the problem of coal gangue accumulation. After being treated with the reagent or method of the present invention, the raw material for preparing concrete can reach more than 60%, which has an unexpected technical effect.

[0093] Example 2

[0094] On the basis of Example 1, a method for decarbonization, modification and activation of unburned coal gangue is provided, the method comprising: chemical decarbonization, modification and activation treatment, the chemical decarbonization, modification and activation treatment comprising: treating the unburned coal gangue with the unburned coal gangue decarbonization, modification and activation agent to obtain decarbonization, modification and activation gangue slurry.

[0095] Furthermore: the method also includes: physical decarbonization and / or mechanical activation, and the coal gangue is first treated with physical decarbonization and / or mechanical activation, and then chemical decarbonization modification and activation treatment is performed after the treatment.

[0096] Preferably, the method may include any one of the following:

[0097] 1.①Physical decarburization is first performed, followed by mechanical activation, and finally chemical decarburization modification and activation;

[0098] Or, ② first carry out mechanical activation, and then carry out chemical decarburization modification activation;

[0099] Further: the physical decarbonization is to separate the coal and the gangue with the first carbon content by photoelectric separation, or to obtain the gangue with the first carbon content by screening, wet separation, gravity separation, etc.;

[0100] The mechanical activation is to hammer the gangue and then further grind it to obtain an activated gangue material with a first particle size;

[0101] The chemical decarbonization modification and activation is to use the coal gangue chemical decarbonization modification and activation agent to carry out chemical decarbonization modification and activation treatment; after the chemical decarbonization modification and activation, a modified and activated low-carbon gangue slurry with a carbon content of the second carbon content is obtained.

[0102] The mechanical activation is to hammer and ball-mill the first carbon content gangue obtained after physical decarbonization of Class I, Class II, Class III coal gangue and photoelectric sorting, or screening, wet sorting, gravity sorting, etc., to achieve activated gangue material with a first particle size.

[0103] Chemical decarbonization modification and activation: using the chemical decarbonization modification activator described in Example 1, the activated gangue of the first particle size obtained after physical decarbonization is subjected to decarbonization modification and activation treatment; after the chemical decarbonization modification and activation, an activated low-carbon gangue having a carbon content of the second carbon content is obtained;

[0104] The most important factors affecting the physical properties of autoclaved aerated concrete prepared from coal gangue are the carbon content of the raw materials and the activity of mineral components such as silicon oxide, aluminum oxide, and calcium oxide. Therefore, it is necessary not only to reduce the carbon content of coal gangue, but also to modify and activate the coal gangue as much as possible.

[0105] In the above method, if the coal gangue raw material already meets the first carbon content, the mechanical activation + chemical decarbonization modification activation treatment method can be directly used, and photoelectric separation, or physical decarbonization methods such as screening, wet separation, gravity separation, and flotation are no longer required.

[0106] The three types of coal gangue with higher carbon content can also be directly treated by chemical decarbonization modification and activation methods, but direct treatment cannot recover coal with higher carbon content, which will cause waste of energy resources.

[0107] The screening, wet separation, gravity separation and flotation methods can be adopted but not limited to conventional methods, which will not be described in detail here.

[0108] The following specific implementation steps are used as examples to illustrate the method of the present invention, but should not be regarded as limiting the present invention:

[0109] ① Physical decarbonization: Physical treatment methods to reduce the carbon content of coal gangue include electro-optical separation, screening, wet separation, gravity separation, flotation and other conventional physical decarbonization methods.

[0110] ② Mechanical activation: The coal gangue with the first carbon content is subjected to deep fine grinding after being hammered to achieve a first particle size; the deep fine grinding is carried out by dry grinding or wet grinding; the first particle size is 180 mesh sieve residue ≤15%.

[0111] The volcanic ash activity of uncalcined gangue is very low. The ball milling refinement process uses mechanical stimulation to activate the activity of gangue. During the ball milling process, the gangue mineral crystal particles can be refined through strong mechanical impact, shearing, grinding, and mutual extrusion and collision between particles. In addition, the mechanical force causes microcracks on the surface and inside of the particles, and the particle surface is defective, making it easier for polar molecules or ions to enter the internal voids of the crystal structure, promoting the depolymerization of silicon oxide and aluminum oxide in the gangue. The most intuitive effect is to refine the particles and increase the specific surface area, greatly improving its efficiency and effect in the hydrothermal synthesis reaction.

[0112] ③ Chemical decarbonization modification and activation: The first carbon content and first particle size of the coal gangue slurry activated by mechanical fine grinding is treated with a mixture including but not limited to sodium nitrate, calcium nitrate, H 2 O 2 It uses chemical methods to oxidize organic carbon in coal gangue mineral crystals, so that coal carbon is stripped from other mineral bodies and partially generates CO 2 , H 2 , O 2 When the gas is volatilized, some of the new substances with small molecules are dispersed in the raw materials, and even completely oxidized to generate carbon dioxide and water, thus changing the physical and chemical properties of the original minerals, especially the mineral crystals with more impurities such as illite, mica, and coal-bed gangue, so that they are stimulated and depolymerized into highly active components such as silicon oxide, aluminum oxide, and calcium oxide, which is beneficial to increase the solubility and participate in the hydrothermal synthesis reaction of the product. And the chemical modification activator has no other adverse effects on the inorganic mineral raw materials in the coal gangue.

[0113] Therefore, the chemical modification and activation method not only expands the tolerance of the carbon content of coal gangue, but also effectively stimulates and improves the activity of coal gangue raw materials, further improves the hydrothermal synthesis reaction efficiency of the product, promotes the improvement of the microporous structure of autoclaved aerated concrete, and thus improves the physical properties of autoclaved aerated concrete products. It has the functions of decarbonization, activation and promotion of the microporous structure content of the product in one step, so it has great innovative significance.

[0114] The unburned coal gangue decarbonization modification and activation method of the present invention, by combining physical decarbonization, mechanical activation, chemical decarbonization modification and activation and other composite decarbonization modification and activation methods, on the one hand improves the utilization rate of coal gangue, and increases the amount of coal gangue used in autoclaved aerated concrete, so that coal gangue can be effectively recycled, saving the cost of raw materials for autoclaved aerated concrete, and solving the environmental problem of stacking coal gangue. On the other hand, it expands the tolerance of the autoclaved aerated concrete manufacturing process to the carbon content of coal gangue materials, effectively stimulates and improves the activity of coal gangue raw materials, further improves the hydrothermal synthesis reaction effect of the product, and promotes the increase of the content of the microporous structure of the product, thereby improving the physical properties of the autoclaved aerated concrete product. It has the effects of decarbonization treatment, activation treatment and promoting the increase of the content of the microporous structure of the product in one step, so it has great innovative significance.

[0115] Example 3

[0116] On the basis of Example 1 or 2, further: the first carbon content is less than 20%; for example, it can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, and the present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0117] The second carbon content is less than 3%, for example, it can be 1%, 1.5%, 2%, 2.5%, 3%, and the present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0118] In the mechanical activation, the grinding and refining adopts dry grinding or wet grinding; the first particle size is: 180 mesh sieve residue ≤ 15%.

[0119] Uncalcined coal gangue is inactive or has very low activity. The ball milling refinement process uses mechanical excitation, mechanical-chemical composite excitation and other means to stimulate the activity of coal gangue. During the ball milling process, the coal gangue mineral crystal particles can be refined through strong mechanical impact, shearing, grinding, and mutual extrusion and collision between particles; in addition, the mechanical force causes microcracks on the surface and inside of the particles, and the particle surface is defective, making it easier for polar molecules or ions to enter the internal voids of the crystal structure, promoting the depolymerization of silicon oxide, calcium oxide and aluminum oxide in the coal gangue. The most intuitive effect is to refine the particles and increase the specific surface area, greatly improving its efficiency and effect in the hydrothermal synthesis reaction.

[0120] By using the method of chemical decarbonization modification and activation, the silicon oxide, aluminum oxide, calcium oxide and other components contained in the gangue can be fully activated. These activated components can fully participate in the hydrothermal reaction of the product, thereby improving the physical properties of the concrete products.

[0121] Further: the chemical decarbonization modification and activation method is to add the coal gangue chemical decarbonization modification agent to the slurry of the activated gangue material of the first particle size according to the above usage amount, and stir it at a temperature of 60 to 80° C. until it undergoes a sufficient oxidation reaction to obtain the modified activated low-carbon gangue slurry;

[0122] The amount of the activation agent for chemical decarbonization modification of coal gangue is 1% to 7% of the total mass of the coal gangue before addition, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, and the present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0123] Further, the chemical decarbonization modification activation method is to use, according to the above usage amount, the mechanically finely ground activated coal gangue slurry with a carbon content still in the first carbon content and a particle size of the first particle size, including but not limited to sodium nitrate, calcium nitrate, H 2 O 2 One of the strong oxidants is stirred at a temperature of 60 to 80°C until a sufficient reaction is carried out to obtain the decarbonized modified activated gangue slurry, which generally needs to be stirred for more than 60 minutes. The decarbonized modified activated gangue slurry obtained can be stored in a slurry tank for standby use. When stored for standby use, it needs to be stirred to avoid precipitation. At the same time, the organic carbon that is not completely oxidized in the slurry and the small molecular organic matter produced by carbon oxidation continue to be oxidized in the slurry tank until it is completely decomposed into CO 2 and H 2 O.

[0124] Further: the chemical decarbonization modification activation treatment is to add the unburned coal gangue decarbonization modification activator to the unburned coal gangue according to the above-mentioned usage amount, stir it at a temperature of 60°C to 80°C until it is fully reacted, and obtain the decarbonization modification activation gangue slurry with a carbon content of less than 3%, and the decarbonization modification activation gangue slurry contains:

[0125] Silicon oxide 30% to 90%, for example, can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, the present invention is not limited to the listed values, other values ​​not listed within the numerical range are also applicable;

[0126] Aluminum oxide 0.2% to 45%, for example, can be 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, the present invention is not limited to the listed values, other values ​​not listed within the numerical range are also applicable;

[0127] Calcium oxide 0.05% to 20%, for example, can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, the present invention is not limited to the listed values, other values ​​not listed within the numerical range are equally applicable.

[0128] The carbon content below 3% may be, for example, 1%, 1.5%, 2%, 2.5%, or 3%. The present invention is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0129] Example 4

[0130] On the basis of any one of Examples 1-3, an autoclaved aerated concrete prepared from unburned coal gangue, wherein the ingredients of the autoclaved aerated concrete prepared from unburned coal gangue are:

[0131] Use a decarbonized modified activated gangue slurry with a mass content greater than or equal to 50%, and the decarbonized modified activated gangue slurry is obtained by the method described in Example 3; the mass content is greater than or equal to 50%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., and the present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0132] The calcium / silicon ratio of the ingredients is 0.5 to 1.0; for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1. The present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0133] When the pores in autoclaved aerated concrete are small and evenly distributed, they generally have a better ability to resist external loads, which is manifested as high compressive strength of the product. On the contrary, if the pores are large (such as greater than 2mm) and unevenly distributed, it is easy to cause stress concentration under the action of external loads, resulting in premature destruction of certain pore wall structures in the product and reduced product strength. Therefore, while keeping the porosity unchanged, reducing the pore (macro, visible) content and increasing the micropore content is an effective way to improve the strength of autoclaved aerated concrete.

[0134] The porosity of B07 products is 68% to 71%, the porosity of B06 products is 72% to 76%, and the porosity of B05 products is 77% to 80%. The existence of these pores changes the compactness of the products, which will reduce the strength, but improve the thermal insulation performance and frost resistance.

[0135] The porosity of autoclaved aerated concrete mainly depends on the amount of aluminum powder added, which in turn determines the dry density of the autoclaved aerated concrete. In the present invention, the amount of aluminum powder used is reduced by about 10% compared with the conventional formula, but according to the density of the final product, it can be seen that the porosity is not reduced, indicating that the unburned coal gangue decarbonization modification activator of the present invention has the effect of increasing the porosity.

[0136] Through experimental observation, it can be found that the pores formed by the pore wall material inside the autoclaved aerated concrete can be divided into two categories: macropores and micropores.

[0137] Large pores are visible to the naked eye and are also called macroscopic pores. They are formed by bubbles, so they are usually called pores. Pores are formed by the gas-generating materials such as aluminum powder in the slurry. During the static process, the slurry gradually hardens and fixes in the blank. The size of the pores ranges from about 2mm to less than 0.8mm.

[0138] Micropores, also called microscopic pores, exist in the pore walls and can only be clearly observed under microscopes and electron microscopes. They include capillary pores, gel pores and intercrystalline pores. Under an electron microscope or scanning electron microscope, the intracrystalline pores between gel particles, the so-called ultra-micropores, can also be seen. Capillary pores generally have a radius of 100μm to 5nm and are formed by the evaporation of capillary water. Gel pores and intercrystalline pores are between colloid and crystal particles. Due to the discontinuity of particles, they exist in a smaller size, generally 1 to 5nm. Ultra-micropores are even smaller, usually below the scale of colloid particles, and exist due to the uneven internal structure of colloid particles. The water in these pores, except for the water in the pores above the capillary, which can evaporate (hence called condensed water), the water in other micropores mostly participates in the formation of the pore wall structure to a certain extent in some form, or becomes part of its structure, such as adsorbed water (or gel water) and interlayer water, which are non-evaporable water. Without these water, the internal structure of the material will lose balance and be destroyed. Further: the hydrothermal synthesis product contained in the autoclaved aerated concrete prepared from the unburned coal gangue comprises hydrated mineral crystals, and the hydrated mineral crystals include any combination of CSH (I), tobermorite, aluminum-substituted tobermorite, hydrogarnet, xonotlite, and calcium sulfoaluminate hydrate, such as Figure 5 shown.

[0139] The role of coal gangue in autoclaved aerated concrete is to provide siliceous materials for hydrothermal synthesis reaction. At room temperature, the crystal structure of siliceous materials is stable and in a state of minimum internal energy, making them inert materials. During high-temperature hydrothermal treatment, the siliceous materials (SiO 2 ) increases its solubility and reacts with the calcium material CaO in the raw materials (cement, lime) to form hydration products such as calcium silicate hydrate gel (CSH). Calcium silicate hydrate is a calcium silicate hydrate mineral with a chemical formula of Ca 5 Si 6 O 16 (OH)·4H 2 O. CSH(I) is one of the most important hydrates in silicate concrete. It is a monobasic calcium silicate hydrate with low crystallinity and high compressive strength. It can be synthesized from lime and quartz sand or lime and silica gel in a short time under autoclaving conditions of 125-175°C (lime and silica gel can also be synthesized at room temperature in a longer time). Due to the presence of various impurities in the main raw materials, the resulting cementitious material cannot be just a pure hydration product of CSH(I), but a mixture of various hydration products or continuous phases of various compositions of calcium silicate hydrate, calcium aluminate, calcium sulfoaluminate, etc. Under autoclaving curing (175°C-195°C, 0.9-1.4Mpa saturated steam curing), a large amount of single-crystal CSH(I) is transformed into coarse-crystal tobermorite, thereby stabilizing and improving the performance of the product.

[0140] From the perspective of product strength and the microscopic perspective of crystal intergrowth, in the mineral composition of autoclaved aerated concrete products prepared from unburned coal gangue, the more low-alkalinity calcium silicates (such as tobermorite, xonotlite, orthorhombic calcium silicate, CSH single crystal, etc.) have extremely small crystal size, large specific surface area, many crystal intergrowth contact points, and strong connection between particles, the more high-alkalinity hydrated calcium silicates (such as C 6 S 3 H.C 3 S 2 H.C 2 SH, C 3 SH 2 The less the amount of hydrated calcium silicate and other hydrated minerals, the more dense the microcrystalline structure can be. The strength and durability of the product can reach a better level. This is the reason why the autoclaved aerated concrete product prepared from the unburned coal gangue of the present invention achieves high strength and long-term durability.

[0141] Furthermore: the autoclaved aerated concrete prepared from the unburned coal gangue forms a heterogeneous solid-liquid-gas multiphase stacking structure with inner core particles of siliceous material as the skeleton, hydrated silicate as the colloid, connected and supported by crystal intergrowths, and including a variety of micropores.

[0142] Example 5

[0143] The following is a method for preparing autoclaved aerated concrete using unburned coal gangue after decarbonization modification according to the present invention with specific steps:

[0144] (1) Mixing ingredients: Mixing the modified activated gangue slurry described in Example 4 with calcium materials such as lime, cement, and regulating materials according to a preset formula to obtain a mixed slurry, wherein the mixed slurry contains more than 50% of the activated gangue material described above; and the calcium / silicon ratio in the mixed slurry is 0.5 to 1.0;

[0145] (2) Pouring and stopping: continue to stir the slurry and add the gas generating agent, quickly inject it into the steel mold, and send it into a constant temperature and humidity chamber to stop gas generation;

[0146] (3) Cutting and demoulding: After removing the bread head that is higher than the mold by wire cutting, demoulding is performed to obtain the green body;

[0147] (4) Pre-curing before autoclave: sending the green body into a constant temperature and humidity chamber for pre-curing before autoclave;

[0148] (5) Autoclave curing: The green body that has been pre-cured before being put into an autoclave for autoclave curing.

[0149] Preferably, the static temperature is 50-65°C, the humidity is 90-95°C, and the time is 2.5-4.5h.

[0150] Preferably, the pre-curing temperature before the autoclave is 60-80°C, the humidity is 90-95 degrees, and the time is 2-4 hours.

[0151] Preferably, the autoclave curing conditions are:

[0152] The first stage: the temperature is raised from room temperature to 105℃ at a constant speed for 10 minutes; the second stage: the temperature is raised from 105 to 125℃ at a constant speed for 75 minutes

[0153] Since the laboratory uses a small autoclave, steam is gradually heated by heating water at room temperature with an electric heating tube. There is air in the autoclave, and the equipment does not have a vacuum pumping measure, so the air needs to be exhausted for better results. Therefore, it takes 10 minutes from room temperature to 105°C. The third stage: the temperature is uniformly raised from 125 to 190°C for 75 minutes;

[0154] The fourth stage: maintain the kettle at a constant temperature of 190℃ and a pressure of 1.30MPa for 8 to 12 hours, then exhaust and reduce the pressure and temperature at a uniform rate for 2 hours until the pressure in the kettle drops to 0, and then take the kettle out after the temperature in the kettle drops to a safe temperature below 60℃.

[0155] The gas generation and quiescence is to ensure a series of physical changes such as gas generation, thickening, and initial setting of the slurry to form a green body with suitable strength; pre-curing before the autoclave is to prevent the heat dissipation and cooling of the green body before waiting for autoclave curing after demoulding and cutting, and to improve the strength of the green body entering the autoclave; autoclave curing is a specific way and means to promote the green body to complete the necessary physical and chemical changes - hydrothermal synthesis reaction, generate the required new minerals, and enable the product to obtain good physical and mechanical properties. The biggest difference between aerated concrete and ordinary concrete is that the hydration reaction is basically completed in the autoclave, and the autoclave curing time determines the final formation of the intrinsic properties of aerated concrete.

[0156] During the autoclave curing process, the SiO 2 、Al 2 O 3 , CaO undergo hydrothermal reaction to produce various hydration products, which are key factors in the performance of finished autoclaved aerated concrete products. After being treated with the chemical decarbonization modification activation reagent of the present invention, SiO 2 、Al 2 O 3 , CaO is more active, which further enhances the effect of the above-mentioned hydrothermal reaction, thereby obtaining a denser microcrystalline structure, so that the strength, durability and other properties of the product reach a better level.

[0157] The autoclave curing temperature system is based on the CaO, SiO 2 、Al 2 O 3 、CaSO 4 The temperature conditions required for the hydrothermal synthesis reaction of the main components and their products follow the specific control system of temperature, pressure and time formulated for the full and effective curing of the autoclaved aerated concrete body, so as to achieve full and reasonable curing of the body, so that the product can obtain the best strength in a shorter time, while minimizing the possible damage to the body.

[0158] Example 6

[0159] Experimental Example 1 (Formula and preparation process of 1# raw material + chemically modified activator):

[0160] 1# raw material: carbon content 3.7%, calorific value 260kcal / kg; formula C / S = 0.82;

[0161] (1) Chemical decarbonization modification and activation treatment: 62 parts of 1# material, 2% calcium nitrate by mass fraction of gangue, and 0.65 parts of 60°C warm water were added and stirred for 60 minutes;

[0162] (2) While stirring continuously, quickly add 17 parts of lime, 18 parts of cement, and 3 parts of gypsum and continue stirring for 2.5 minutes;

[0163] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0164] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0165] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3.0 to 4.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0166] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0167] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 4 hours;

[0168] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ constant temperature rise for 10min (during which the vent valve is open to discharge the air in the autoclave), 105 ~ 125℃ constant temperature rise for 75min, 125 ~ 190℃ constant temperature rise for 75min, 190℃ (autoclave pressure 1.3MPa) constant temperature for 8h, exhaust gas and reduce pressure and temperature for 2h until the autoclave pressure drops to 0. After the humidity in the autoclave drops to a safe temperature below 60℃, take out of the autoclave.

[0169] The absolute dry density is 534kg / m 3 Its compressive strength reaches 2.76Mpa, which is greater than the average value requirement of national standard strength level A2.5 and dry density level B05.

[0170] Note: Step (1) can be carried out independently. The obtained decarbonized modified activated gangue slurry can be stored and used as a raw material for preparing autoclaved aerated concrete. After 60 minutes of reaction in step (1), the subsequent steps can be carried out, or the slurry can be stored in a slurry storage tank and kept stirred in the slurry storage tank. The modification and activation reaction of the slurry will continue.

[0171] Experimental Example 2 (Formula and preparation process of 1# raw material + 2% chemical modified activator + 3% silica fume):

[0172] 1# raw material: carbon content 3.7%, calorific value 260kcal / kg; formula C / S = 0.80;

[0173] (1) Chemical decarbonization modification and activation treatment: 59 parts of 1# material, 2% calcium nitrate by mass fraction of gangue, 3 parts of silica fume, and 0.65 parts of 60°C warm water were added and stirred for 90 minutes;

[0174] (2) While stirring continuously, quickly add 17 parts of lime, 18 parts of cement, and 3 parts of gypsum and continue stirring for 2.5 minutes;

[0175] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0176] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0177] (5) The poured mold is then placed in a constant temperature and humidity chamber at 50°C and 95% relative humidity for 2.5 to 3.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0178] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0179] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 3 hours;

[0180] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ constant temperature rise for 10min (during which the vent valve is in the open state to discharge the air in the autoclave), 105 ~ 125℃ constant temperature rise for 75min, 125 ~ 190℃ constant temperature rise for 75min, 190℃ (autoclave pressure 1.3MPa) constant temperature for 8h, exhaust gas and reduce pressure and temperature for 2h until the autoclave pressure drops to 0. After the humidity in the autoclave drops to a safe temperature below 60℃, take out of the autoclave.

[0181] The absolute dry density is 537kg / m 3 Its compressive strength reaches 2.89Mp, which is greater than the average value requirement of national standard strength level A2.5 and dry density level B05.

[0182] Experimental Example 3 (Formula and preparation process of 2# raw material + 3% chemically modified activator):

[0183] 2# raw material: carbon content 7.5%, calorific value 525kcal / kg; formula C / S=0.92.

[0184] (1) Chemical decarbonization modification and activation treatment: 64.5 parts of 2# raw material, 3% sodium nitrate by mass fraction of gangue, and 0.75 parts of 60°C warm water were added and stirred for 120 minutes;

[0185] (2) While stirring continuously, quickly add 20 parts of lime, 12 parts of cement, and 3.5 parts of gypsum and continue stirring for 2.5 minutes;

[0186] (3) Add 0.09 parts of aluminum powder while stirring for 40 seconds;

[0187] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0188] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3.5 to 4.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0189] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0190] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 4 hours;

[0191] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ constant temperature rise for 10min (during which the vent valve is in the open state to discharge the air in the autoclave), 105 ~ 125℃ constant temperature rise for 75min, 125 ~ 190℃ constant temperature rise for 75min, 190℃ (autoclave pressure 1.30MPa) constant temperature for 8h, uniform exhaust and depressurization for 2h until the autoclave pressure drops to 0. After the humidity in the autoclave drops to a safe temperature below 60℃, take out of the autoclave.

[0192] The absolute dry density is 598kg / m 3 Its compressive strength reaches 3.12Mpa, meeting the minimum requirements of national standard strength level A3.5 and dry density level B06.

[0193] Experimental Example 4 (Formula and preparation process of 2# raw material + 3% chemical modified activator + 3% silica fume):

[0194] 2# raw material: carbon content 7.5%, calorific value 525kcal / kg; formula C / S=0.88.

[0195] (1) Chemical decarbonization modification and activation treatment: 61.5 parts of 2# raw material, 3% sodium nitrate based on the mass of gangue, 3 parts of silica fume, 0.75 parts of 60°C warm water, and stirred for 120 minutes;

[0196] (2) While stirring continuously, quickly add 20 parts of lime, 12 parts of cement, and 3.5 parts of gypsum and continue stirring for 2.5 minutes;

[0197] (3) Add 0.08 parts of aluminum powder while stirring for 40 seconds;

[0198] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0199] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 3.0 to 4.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0200] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0201] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80°C and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 4 to 6 hours;

[0202] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ constant temperature rise for 10min (during which the vent valve is in the open state to discharge the air in the autoclave), 105 ~ 125℃ constant temperature rise for 75min, 125 ~ 190℃ constant temperature rise for 75min, 190℃ (autoclave pressure 1.30MPa) constant temperature for 8h, uniform exhaust and depressurization for 2h until the autoclave pressure drops to 0. After the humidity in the autoclave drops to a safe temperature below 60℃, take out of the autoclave.

[0203] The absolute dry density is 630kg / m 3 Its compressive strength reaches 3.57Mpa, meeting the national standard strength level A3.5 and dry density level B06 average value requirements.

[0204] Experimental Example 5 (Formula and preparation process of 3# raw material + 5% chemically modified activator):

[0205] 3# raw material: carbon content 15.4%, calorific value 1080kcal / kg; formula C / S = 0.88

[0206] (1) Chemical decarbonization modification and activation treatment: 60 parts of 3# raw material, 6 parts of silica fume, 5% sodium percarbonate by mass fraction of gangue, 0.75 parts of 60°C warm water, and stir for 120 minutes;

[0207] (2) While stirring continuously, quickly add 16 parts of lime, 16 parts of cement, and 2.0 parts of gypsum and continue stirring for 2.5 minutes;

[0208] (3) Add 0.08 parts of aluminum powder while stirring for 40 seconds;

[0209] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0210] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 2.5 to 3.5 hours to complete the static stop processes of foaming, shaping, and solidification;

[0211] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0212] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 2 to 4 hours;

[0213] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ constant temperature rise for 10min (during which the vent valve is in the open state to discharge the air in the autoclave), 105 ~ 125℃ constant temperature rise for 75min, 125 ~ 190℃ constant temperature rise for 75min, 190℃ (autoclave pressure 1.30MPa) constant temperature for 8h, uniform exhaust and depressurization for 2h until the autoclave pressure drops to 0. After the humidity in the autoclave drops to a safe temperature below 60℃, take out of the autoclave.

[0214] The absolute dry density is 634kg / m 3 Its compressive strength reaches 3.02Mpa, meeting the minimum requirements of national standard strength level A3.5 and dry density level B06.

[0215] Experimental Example 6 (Formula and preparation process of 3# raw material + 5% chemical modified activator + 8# silica fume):

[0216] 3# raw material: carbon content 15.4%, calorific value 1080kcal / kg; formula C / S=0.86.

[0217] (1) Chemical decarbonization modification and activation treatment: 58 parts of 3# raw material, 8 parts of silica fume, 5% hydrogen peroxide by mass fraction of gangue, 0.75 parts of 60°C warm water, and stirred for 120 minutes;

[0218] (2) While stirring continuously, quickly add 16 parts of lime, 16 parts of cement, and 2 parts of gypsum and continue stirring for 2.5 minutes;

[0219] (3) Add 0.08 parts of aluminum powder while stirring for 40 seconds;

[0220] (4) After stopping stirring, quickly inject the stirred slurry into the steel mold prepared in advance;

[0221] (5) The poured mold is then placed in a constant temperature and humidity chamber at 60°C and 95% relative humidity for 2.5 to 3.0 hours to complete the static stop processes of foaming, shaping, and solidification;

[0222] (6) Then use a wire saw to cut off the bread head that is higher than the mold and demould it;

[0223] (7) The demoulded green body is sent to a constant temperature and humidity chamber at a temperature of 80° C. and a relative humidity of 95% for further pre-curing (pre-kettle pre-curing) for 2 to 4 hours;

[0224] (8) The pre-cured green body is quickly sent to the experimental small autoclave for autoclave curing. The curing system is: room temperature ~ 105℃ constant temperature rise for 10min (during which the vent valve is in the open state to discharge the air in the autoclave), 105 ~ 125℃ constant temperature rise for 75min, 125 ~ 190℃ constant temperature rise for 75min, 190℃ (autoclave pressure 1.30MPa) constant temperature for 8h, uniform exhaust and depressurization for 2h until the autoclave pressure drops to 0. After the humidity in the autoclave drops to a safe temperature below 60℃, take out of the autoclave.

[0225] The absolute dry density is 650kg / m 3 Its compressive strength reaches 3.63Mpa, meeting the national standard strength level A3.5 and dry density level B06 average value requirements.

[0226] Comparative Example 1:

[0227] The steps of Experimental Example 1 are the same as those of Experimental Example 1 except that the gangue slurry is not treated with a modified activator. The absolute dry density is 539 kg / m 3 When the compressive strength reaches 2.32Mpa, it is lower than the compressive strength of the product in Example 1.

[0228] Comparative Example 2:

[0229] The steps of Experimental Example 3 are the same as those of Experimental Example 3 except that the gangue slurry is not treated with a modified activator. The absolute dry density is 523 kg / m 3 When the compressive strength reaches 2.01Mpa, it is lower than the compressive strength of the product in Example 3.

[0230] Comparative Example 3:

[0231] The steps of Experimental Example 5 are the same as those of Experimental Example 5 except that the gangue slurry is not treated with a modified activator. The absolute dry density is 616 kg / m 3 When the compressive strength reaches 1.66Mpa, it is lower than the compressive strength of the product in Example 5.

[0232] Table 1 Relationship between autoclaved aerated concrete performance and process

[0233]

[0234]

[0235] From Table 1 we can see that:

[0236] Experimental Example 1 uses the chemical decarbonization modification method of the present invention, and the compressive strength of the autoclaved aerated concrete obtained is significantly improved compared with the comparative example 1 which does not use the chemical decarbonization modification method under the same conditions, and the specific strength is increased by 20.10%; and in Experimental Example 2 in which the regulating agent silica fume is added on the basis of Experimental Example 1, the compressive strength is further improved, and the specific strength is increased by 3.58% on the basis of Experimental Example 1; the specific strength of Experimental Example 2 is increased by 25.05% on the basis of Comparative Example 1.

[0237] Experimental Example 3 uses the chemical decarbonization modification method of the present invention, and the compressive strength of the autoclaved aerated concrete obtained is significantly improved compared with Example 2 which does not use the chemical decarbonization modification method under the same conditions, and the specific strength is increased by 42.74%; and in Experimental Example 4 in which the regulating agent silica fume is added on the basis of Experimental Example 3, the compressive strength is further improved, and the specific strength is increased by 8.63% on the basis of Experimental Example 3; the specific strength of Experimental Example 4 is increased by 55.05% on the basis of Comparative Example 2.

[0238] Experimental Example 5 uses the chemical decarbonization modification method of the present invention, and the compressive strength of the autoclaved aerated concrete obtained is significantly improved compared with the comparative example 3 which does not use the chemical decarbonization modification method under the same conditions, and the specific strength is increased by 76.73%; and in Experimental Example 6 in which the regulating agent silica sol is added on the basis of Experiment 5, the compressive strength is further improved, and the specific strength is increased by 17.26% on the basis of Experiment 5; on the basis of comparative example 3, the specific strength of Experimental Example 6 is increased by 107.24%, indicating that the combined use of multiple regulating agents can further improve the strength of the product.

[0239] The products prepared by the method of the present invention can meet the compressive strength requirements of the corresponding dry density level in the national standard GB / T11968-2020 (see Table 4). At the same time, under the same chemical modification treatment method, the lower the carbon content of the original coal gangue material, the better the compressive strength of the prepared autoclaved aerated concrete after chemical modification, which illustrates the importance of decarbonization treatment. For the 3# raw material with a higher carbon content (carbon content of about 15.4%), qualified products cannot be prepared without chemical modification. For coal gangue with a carbon content of about 10%, the chemical decarbonization modification method of the present invention makes it possible to use the coal gangue with the above carbon content as the raw material of autoclaved aerated concrete, and realizes a higher proportion of utilization for the resource application of coal gangue.

[0240] Figure 1-1 The samples of Experimental Example 1 and Experimental Example 2 were prepared by adding chemical modifiers to 1# coal gangue raw materials. In Experimental Example 2, other modifiers were added to further improve the strength of the product.

[0241] Figure 1-2The samples of Experimental Example 3 (H3) and Experimental Example 4 (H4) were prepared by adding chemical modifiers to 2# coal gangue raw materials. Among them, Experimental Example 4 (H4) added other modifiers to further improve the strength of the product;

[0242] Figure 1-3 The sample (15-2) of Experimental Example 5 was prepared by adding a chemical modifier to the 3# coal gangue raw material.

[0243] Figure 1-4 The sample of Experiment 6 is prepared by adding other regulators to the raw material of Experiment 5.

[0244] Figure 2 This is a 40-fold magnified observation photo of 2# coal gangue raw material, in which the black particles are carbon particles.

[0245] Figure 3 The raw material is 3# coal gangue with a carbon content of about 15.4%. No chemical modification activator is added. After batching, stirring, pouring, stopping, and demoulding, the appearance inspection shows that the sample is unqualified, with poor mechanical strength and uneven bubble distribution. Therefore, no further subsequent processing procedures and inspections are carried out.

[0246] The chemical compositions of No. 1, No. 2 coal and No. 3 coal gangue used in the present invention are shown in Table 2, and the mineral compositions are shown in Table 3.

[0247] Table 2 The chemical composition of the gangue raw material treated by chemical decarbonization modification and activation of the present invention is as follows:

[0248] Coal Gangue <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> CaO MgO <![CDATA[Na 2 The]]> <![CDATA[K 2 The]]> <![CDATA[SO 3 ]]> C 1#(%) 61.79 10.28 5.84 9.07 4.44 0.62 1.80 2.06 3.7 2#(%) 49.23 18.65 7.72 6.20 3.61 0.59 1.74 4.27 7.5 3#(%) 45.25 14.16 6.96 9.05 2.45 0.54 1.90 1.05 15.4

[0249] Table 3 The mineral composition of the gangue raw material treated by chemical decarbonization modification of the present invention is as follows:

[0250]

[0251] Table 4 Compressive strength and dry density requirements

[0252]

[0253] The composition of calcium raw materials of the autoclaved aerated concrete of the present invention is shown in Table 5.

[0254] Table 5 Chemical composition of calcium raw materials of autoclaved aerated concrete of the present invention

[0255]

[0256] Preparation of other raw materials for autoclaved aerated concrete:

[0257] Other materials used in the present invention are as follows:

[0258] plaster:

[0259] This experiment uses sintered masonry desulfurized gypsum.

[0260] Aluminum powder:

[0261] This test uses metal aluminum powder, which is still normally used by most autoclaved aerated concrete companies, as the gas generating agent.

[0262] Silica Fume:

[0263] Provided by a company in Ningxia, SiO 2 Content ≥93%, specific surface area ≥18m 2 / g

[0264] Modifier:

[0265] The modifiers used in the present invention are industrial grade modifiers purchased online, such as sodium nitrate, ammonium nitrate, calcium nitrate, sodium percarbonate, H 2 O 2 .

[0266] Figure 4 This is an XRD spectrum of the 1# coal gangue experimental sample provided by an embodiment of the present invention, and the XRD spectrum shows the main hydration products and unreacted mineral compositions. It can be seen from the figure that the main mineral compositions in the sample are Tobermorite, CSH gel, anhydrite, quartz, dolomite, calcite, scawtite, pseudowoll astonite, halloysite and other minerals. Figure 5 This is a SEM electron microscope photo of a 1# coal gangue experimental sample provided by an embodiment of the present invention; the photo shows the microstructure of the coal gangue experimental sample, wherein the flakes are mineral structures such as tobermorite, the needles are hydration products such as CSH gel, which are beneficial to improving the strength of the product, and the particles are residual minerals that have not reacted completely, such as quartz, dolomite, and calcite, which are distributed relatively evenly.

[0267] The present invention has the following significant innovations:

[0268] (1) Gangue with low carbon content Class I or II (carbon content 6%) or less can be used in autoclaved aerated concrete without further sorting, but the addition of modifiers will further improve its performance;

[0269] (2) The core innovation is to treat coal gangue with chemical modifiers, which not only oxidizes and reduces the carbon content of coal gangue, but also depolymerizes the mineral structure of coal gangue, thereby activating SiO 2 、Al 2O 3 , CaO and other chemical elements are beneficial to its activity in hydrothermal reaction; at the same time, it is found that the formation of micropores in gangue autoclaved aerated concrete products can be promoted by chemical oxidation of gangue, thereby achieving the purpose of improving the physical properties of the products.

[0270] (3) The core innovation is to use the chemically modified and activated coal gangue as mentioned above to replace siliceous materials in autoclaved aerated concrete, which has achieved great success in the industry. The performance of the prepared autoclaved aerated concrete meets the national standard requirements, solving a problem that has not been solved in the industry.

[0271] (4) Significance: It has found a feasible way for the comprehensive high-value resource utilization of coal gangue; it has reduced the dependence on mineral resources such as silica sand for the production of autoclaved aerated concrete green ecological building materials.

[0272] The above is only a representative embodiment of the present invention and is not necessarily the optimal formula. Therefore, it is not intended to limit the present invention, and any modification, equivalent replacement or improvement made by any person skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An unburned coal gangue decarbonization modification activator, Features: The unburned coal gangue decarbonization modification activator comprises: Group 1: Nitrates; and / or, in the second group, peroxides or percarbonates; and / or, group III, permanganate; The amount of the unburned coal gangue decarbonization modification activator used accounts for 1% to 7% of the total mass of the coal gangue.

2. The unburned coal gangue decarbonization modification activator according to claim 1, Features : The nitrate comprises: at least one of sodium nitrate, calcium nitrate and calcium ammonium nitrate; The percarbonate comprises: at least one of sodium percarbonate and calcium percarbonate; The peroxide comprises: H 2 O 2 ; The permanganate includes potassium permanganate.

3. The unburned coal gangue decarbonization modification activator according to claim 1, Features: If the unburned coal gangue decarbonization modification activator is only nitrate, the amount of nitrate used in the total mass of coal gangue is calculated by mass as follows: For coal gangue with carbon content of 0% to 5%, use 1% to 3%; 2% to 5% of coal gangue with a carbon content of 5% to 10%; 3% to 6% of coal gangue with a carbon content of 10% to 15%; For coal gangue with a carbon content of 15% to 20%, 4% to 7% is used.

4. A method for decarbonization, modification and activation of unburned coal gangue, Features: The method comprises: chemical decarbonization modification and activation treatment, wherein the chemical decarbonization modification and activation treatment comprises: treating the unburned coal gangue with the unburned coal gangue decarbonization modification activator according to any one of claims 1 to 3 to obtain a decarbonization modified activated gangue slurry.

5. The method for decarbonization, modification and activation of unburned coal gangue as claimed in claim 4, Features: The method also includes: physical decarbonization and / or mechanical activation, and the coal gangue is first treated with physical decarbonization and / or mechanical activation, and then chemical decarbonization modification and activation treatment is performed after the treatment.

6. The method for decarbonization, modification and activation of unburned coal gangue as claimed in claim 5, Features: The physical decarbonization is to separate coal and gangue by photoelectric separation, and / or to adopt at least one of screening, wet separation and gravity separation to make the carbon content of the gangue reach the first carbon content; The mechanical activation is to hammer the gangue and then further grind it to make the gangue particle size be the first particle size after grinding; After the chemical decarbonization, modification and activation treatment, the carbon content of the gangue in the decarbonization, modification and activation gangue slurry obtained is set to the second carbon content.

7. The method for decarbonization, modification and activation of unburned coal gangue according to claim 6, Features: The first carbon content is less than 20%; the second carbon content is less than 3%; The milling and refining process uses dry milling or wet milling; The first particle size is: 180 mesh sieve residue ≤ 15%.

8. The method for decarbonization, modification and activation of unburned coal gangue as claimed in claim 4, Features: The chemical decarbonization modification and activation treatment is to add the unburned coal gangue decarbonization modification activator to the unburned coal gangue in the amount as claimed in claim 1 or 3, and stir it at a temperature of 60°C to 80°C until it is fully reacted to obtain the decarbonization modified activated gangue slurry with a carbon content of less than 3%, and the decarbonization modified activated gangue slurry contains 30% to 90% silicon oxide, 0.2% to 45% aluminum oxide, and 0.05% to 20% calcium oxide.

9. Autoclaved aerated concrete prepared from unburned coal gangue, Features: The ingredients of the autoclaved aerated concrete prepared from unburned coal gangue are: Using 50% or more by mass of decarbonized modified activated gangue slurry, wherein the decarbonized modified activated gangue slurry is obtained by the method according to any one of claims 4 to 8; The calcium / silicon ratio of the ingredients is 0.5-1.

0.

10. The autoclaved aerated concrete prepared from unburned coal gangue as claimed in claim 9, Features: The hydrothermal synthesis product contained in the autoclaved aerated concrete prepared from the unburned coal gangue comprises hydrated mineral crystals, and the hydrated mineral crystals include any combination of CSH(I), tobermorite, aluminum-substituted tobermorite, hydrogarnet, xonotlite, and hydrated calcium sulfoaluminate.

Citation Information

Patent Citations

  • Coal gangue load-type zero-valent iron nanocomposite and preparation method thereof

    CN103394703A

  • Coal gangue activity exciting agent and preparation method of active coal gangue powder based on coal gangue activity exciting agent

    CN117361914A

  • Coal gangue-based autoclaved aerated concrete block and preparation method thereof

    CN117584242A